Chemotherapy use and survival in older adults with metastatic pancreatic cancer in the combination therapy era. Issue 4 (May 2020) - Jain, Rishi; Vijayvergia, Namrata; Devarajan, Karthik; Lewis, Bianca; Denlinger, Crystal S.; Cohen, Steven J.; Dotan, Efrat
Abstract: Background: While a number of landmark clinical trials have led to the approval of combination chemotherapy regimens for metastatic pancreatic adenocarcinoma (mPC), older patients are underrepresented in these studies. We evaluated changes in practice patterns in the management of mPC among medical oncologists in the combination chemotherapy era (CCE). Methods: A retrospective analysis of patients treated at a tertiary cancer center between 2000 and 2015 was conducted. The cohort was divided into two groups (Pre-CCE, diagnosed with mPC between 2000 and 2009 and Post-CCE, diagnosed between 2010 and 2015). Fisher's exact test was used to compare categorical variables. Univariate (UVA) and multivariate analyses (MVA) were conducted to determine the impact of treatment and prognostic variables on survival. Results: 473 older patients with mPC were identified. Post-CCE, there were statistically significant increases in the use of chemotherapy ( p  < .005). While usage of gemcitabine was similar between groups, use of fluoropyrimidines, platinum, taxanes, and irinotecan increased Post-CCE. Use of chemotherapy conferred a modest but significant survival benefit (5 months Pre-CCE versus 6 months Post-CCE, p  < .005). UVA and MVA showed significantly improved survival when older patients were treated with 2 or more chemotherapeutic agents. Conclusions: Despite the limited data available to guide clinicians on optimal usage of these treatments in older patients, medical oncology practice patterns for mPC have changed at an academic cancer center. Increases in chemotherapy use seems to confer a small survival benefit. Additional prospective data in older patients is necessary to improve our management of older patients with mPC.